Risco ocupacional frente à manipulação de quimioterápicos antineoplásicos: percepção de enfermeiros - Bin, Aline (2017)
The increasing number of new cases of cancer in Brazil and in the world, results in the increase in the demand in specialized services that offer the specific treatment, being, antineoplastic chemotherapy the most used treatment. However, such medications offer potential undesirable effects, with risks in all processes of use and handling of antineoplastic drugs, exposing the environment and health professionals. Thus, nursing professionals working in sectors for oncological treatment, are exposed to chemical risk, especially at the moments of manipulation, administration, handling of the patient's fluids and excreta as well as accidental exposure of chemotherapeutics. The present study had as objective to know the perception of the nurses on the exposure to occupational risks before the manipulation of antineoplastic chemotherapeutics. It is characterized as a qualitative research, of descriptive exploratory type. Nurses who work in a Chemotherapy Outpatient Unit of an university hospital participated of the research. Data were collected using a sociodemographic data survey, non-participant systematic observation, and focus groups. Data analysis was performed through the Thematic Content Analysis. All ethical aspects were respected according to Resolution 466 of December 2012 of the National Health Council, and the project was approved by the Research Ethics Committee under CAAE No. 64517416.8.0000.5346. . After analyzing the data, the following thematic categories emerged: 'Occupational risk in the Chemotherapy Outpatient Clinic: from invisibility to risk perception' and 'Safe Environment and Chemical Risk:' I need more than personal protective equipment (PPE) in the chemotherapy outpatient clinic'. In the first category, aspects related to the perception of occupational risk arise due to the use of antineoplastic chemotherapeutic agents, factors that facilitate the exposure and use of PPE. In the second category, the chemical risk in the Chemotherapy Outpatient Clinic is related to the work environment, structure and services to support the worker's health. Therefore, it is concluded that the chemical risk is recognized by nurses and that the use of PPE is assigned to individual choice and awareness, suggesting the strengthening of mechanisms that favor reflection on the importance of their protection. It is also proposed the narrowing and strengthen of ties between the institution's health worker support structures and the nurses to consolidate practices and a safe environment.